Transforming Rural Non-Farm Livelihoods : The NRLM Journey - Gupta, Arshia (World Bank, Washington, DC, 2020)
Rural India is primarily an agri-based economy. Over-dependence on agriculture has meant declining percapita rural income which has gradually initiated a shift towards the non-farm sector. This transition from agriculture to non-farm sectors is considered an important source of economic growth. DAY-NRLM, which has been instrumental in reaching out to sixty-eight million rural poor women, witnessed a similar shift towards non-agricultural sources of income. This trend encouraged DAY-NRLM to adopt dedicated entrepreneurship promotion measures. Even though, NRLM is more than a decade old, enterprise development programmes have been initiated only in the last five years. These initiatives are expected to gain pace and momentum through National rural economic transformation project (NRETP), which aims to identify existing enterprises with growth potential and provide dedicated services to help them scale-up.